Co–Ni alloy supported on CeO2 as a bimetallic catalyst for dry reforming of methane. (28th February 2020) - Turap, Yusan; Wang, Iwei; Fu, Tiantian; Wu, Yongming; Wang, Yidi; Wang, Wei
Abstract: Dry reforming of methane (DRM) is an effective route to convert two major greenhouse gas (CH4 and CO2 ) to syngas (H2 and CO). Herein, in this work, monometallic Ni/CeO2 and a series of bimetallic Co–Ni/CeO2 catalysts with Co/Ni ratios between 0 and 1.0 have been tested for DRM process at 600–850 °C, atmospheric pressure and a CH4 /CO2 ratio of 1. The catalysts were characterized by X-ray diffraction, hydrogen-temperature programmed reduction, CO2 -Temperature programmed desorption, X-ray photoelectron spectroscopy, and thermogravimetric analysis. The catalyst with a Co/Ni ratio of 0.8 (labeled as 0.8 Co–Ni/CeO2 ) exhibited the highest catalytic activity (CH4 and CO2 initial conversion for 80% and 85% at 800 °C, respectively) and the highest stability (less carbon deposition after 600min). This improved activity can be attributed to the Co–Ni alloy, which formed after reduction. Its weak chemisorption with hydrogen results in inhibition of reverse water gas shift reaction. In addition, Co-promoted the adsorption of surface oxygen enhances carbon removal, making it more stable. Graphical abstract: Image 1 Highlights: CeO2 supported Ni and Co–Ni catalysts were tested for dry reforming of methane. A molar Co/Ni ratio of 0.8 provides the most active and least deactivated catalyst. Co–Ni alloy was formed after reduction, which was responsible for its superior performance.